Knowledge, attitude and practice on dengue fever and its prevention and control measures in urban slums of South India - Nagoor, Khadervali; D., Surendra Babu; Reddy N., Bayapa; Kahn, Shakeer; Kalluri, Reddy Jawaharbasha; John, K. R. (International Journal Of Community Medicine And Public Health, 2017)
Background: Dengue fever (DF) is a viral infection carried by Aedesaegypti. Dengue is one of the major public health concerns and an emergent disease and contributes annual outbreaks in India. The aims and objectives of the study were to know the levels of knowledge regarding causation and modes of transmission Dengue fever in urban slums of Chittoor and to know the levels of awareness and practices regarding the prevention and control measures against dengue fever. Methods: A community based cross sectional study was done in urban slums of Chittoor district in Andhra Pradesh. The data from the family members residing in 100 households of urban slums were randomly selected from the list and interviewed individually. Apart from education and occupation of the participants, information on knowledge about Dengue fever, preventive practices are taken. The results were shown in proportions, percentage and association of the knowledge attitude and practices with the different factors. Results: Over all 100 (males 57 and females 43) people were interviewed with the mean age of 34.5 years. Almost 68% of the individuals knew mosquito causes vector borne diseases irrespective of their educational status and majority of them were daily wagers. Amongst them more than 70% of them were using protective measures. Majority of them responded the probable breeding sites were plastic pots, muddy pots and vessels (38%). The most commonly using protective measures were mosquito repellants (33%) and coils (19%). More than 90% of the individual visit the hospital for health seeking. Conclusions: The awareness regarding dengue and mosquito control measures was satisfactory to an extent. Surveillance along with periodic health education to the community and proper training of health personnel is required.